REDEFINING AMERICAN INTERESTS: ANALYZING US POLICY SHIFTS DURING THE SPACE RACE WITH CHINA (2011-2021) - Yatin, Alika Septiani Eka; Hasbiyalloh, Benni Yusriza; Hanan, Djayadi (Universitas Padjadjaran, 2024)
This research delves into the changing patterns of identity and anarchy culture experienced by the United States in the chronology of the space race with China from 2011 to 2021. Utilizing Alexander Wendt’s constructivist theory, this study explores the transformation in US space policy as a response to China’s growing presence in space exploration. The qualitative methodology employed involves thematic analysis of secondary data sources, including congressional minutes, official statements, media coverage, and public speeches. The findings reveal a dynamic shift in the US’s identity, influenced by its interactions on the international stage. During the Cold War, the US’s identity, shaped by a Hobbesian culture of anarchy, was marked by rivalry with the Soviet Union. Post-Cold War, the focus shifted to demonstrating leadership through international cooperation, reflecting a Kantian logic. However, with the emergence of China as a formidable competitor, the US identity has once again transformed, now characterized by a Lockean culture of competition rather than direct conflict. This shift has led to significant policy reformulations, including strategic partnerships and renewed emphasis on self-reliance in space missions, such as the Artemis program and collaboration with private sector companies like SpaceX. These results highlight the intricate relationship between national identity, perceived threats, and policy responses, underscoring the fluid nature of US space policy in the context of global space contestation.